Analisis Makna Dakwah Film Pendek "Hijab dari Masa Depan" di Channel YouTube Film Maker Muslim - Binti Chadirin, Nadhiroh, M.I.Kom; Ernawati; Tutut Nur Trias Wijayanti (JURNAL KOMUNITAS, 2024)
Da'wah is the activity of spreading religious teachings or messages with the aim of providing understanding and inviting people to do good deeds. In this digital era, the use of visual media is the most effective choice in conveying da'wah. YouTube, as a platform that is currently popular, has become a means for spreading religious messages. Optimal use of the convenience and popularity of YouTube can be done through creating and broadcasting Islamic-based educational content, including films with religious themes. The short film entitled “Hijab dari Masa Depan” is a film that contains many preaching meanings. The aim of this research was to understand the meaning of da'wah in the short film entitled “Hijab dari Masa Depan” on the Muslim Film Maker YouTube channel. This research used qualitative research methods which was structured descriptively. The research results show that the meaning of the denotation in this research was to describe a woman who wanted to wear the hijab but was not ready. The connotations in this short film depict the personal journey of a character who consider or felt interested in wearing the hijab. The meaning of the film Hijab dari Masa Depan was the influence of the environment in making decisions. This could be due to positive environmental encouragement.